2007
DOI: 10.1037/1072-5245.14.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Stress, coping and psychological illness: A cross-cultural study.

Abstract: This cross-cultural research study aimed to explore the relationship of stress and coping with psychological illness or symptoms among university students in Canada and India. The predictor variables were stress (hassles and life experience), 8 ways of coping (Folkman & Lazarus, 1988), and selected personal-social variables, namely, locus of control, self-esteem, and social support. The criterion variables were 9 psychological symptoms of the Brief Symptom Inventory (BSI;Derogatis & Spencer, 1982). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
(33 reference statements)
2
24
0
Order By: Relevance
“…The questionnaire has 53 items that ask participants to describe feelings or thoughts. The reliability, validity, and utility of the BSI have been tested extensively across cultures (Broday & Mason, 1991;Cochran & Hale, 1985;Sinha & Watson, 2007). Cronbach's alpha the BSI in the current study was .96 at time 2.…”
Section: Methodsmentioning
confidence: 75%
“…The questionnaire has 53 items that ask participants to describe feelings or thoughts. The reliability, validity, and utility of the BSI have been tested extensively across cultures (Broday & Mason, 1991;Cochran & Hale, 1985;Sinha & Watson, 2007). Cronbach's alpha the BSI in the current study was .96 at time 2.…”
Section: Methodsmentioning
confidence: 75%
“…In a study by Sinha and Watson (2007), which compared Canadian university students with Indian students, a similar conclusion was drawn. They found that unlike Indians, the use of escape-avoidance coping predicted many psychological symptoms for Canadians.…”
Section: Discussionmentioning
confidence: 60%
“…There are two main reasons why this could be so. First, studies suggest differences between Americans and Asians in stress coping (Bjorck, Cuthbertson, Thurman, & Lee, 2001;Sinha & Watson, 2007). Second, previous research from this laboratory indicates the possibility of cultural variations in Indian military pilots, on characteristics such as achievement, affiliation, and locus of control (Joseph & Ganesh, 2006;Joseph & Kochhar, 2011).…”
Section: Objective Of Researchmentioning
confidence: 88%
“…There are many similarities between NLP and 'The Ways of Coping Questionnaire' (WCQ: Folkman & Lazarus, 1988; recently used by Sinha & Watson, 2007). The WCQ yields eight scores, namely, confronting coping (aggressively trying to change the stressful situation), distancing, self-controlling, seeking social support, accepting responsibility, escape-avoidance, problem-solving and positive reappraisal.…”
Section: What Is Nlp?mentioning
confidence: 99%